Reliability of a device measuring triceps surae muscle fatigability. Issue 2 (23rd March 2004) - Haber, M; Golan, E; Azoulay, L; Kahn, S R; Shrier, I
Abstract : Objective: To examine the test–retest reliability of a protocol using an apparatus designed to standardise the standing heel rise test for the triceps surae muscle. Subjects: 40 healthy subjects volunteered to test short and medium term test–retest reliability (group SM, median age 24 years), and a convenience sample of 38 subjects with a history of unilateral deep vein thrombosis (DVT) volunteered to test long term test–retest reliability (group L, median age 52 years). Design: Subjects carried out 23 heel rises per minute until either the pace or the height could no longer be maintained. Group SM subjects repeated the test 30 minutes later (short term), and again 48 hours later (medium term). Subjects in group L did the test on the unaffected leg, and repeated the test one week later (long term). Results: The median number of heel rises achieved per trial in group SM was 34 (range 16 to 120). The intraclass coefficient (ICC) was 0.93 (SEM 2.1) for both 30 minute and 48 hour test–retest reliability. In group L, the median number of heel rises was 27 (range 9 to 97), with ICC 0.88 and SEM 3.4. Conclusions: The apparatus is a simple and inexpensive standardised tool that reliably measures triceps surae fatigability in subjects with no current injury. Future research should assess its use in injured patients.